Auxarthron ostraviense sp. nov., and A. umbrinum associated with non-dermatophytic onychomycosis - Hubka, Vit; Dobiasova, Stanislava; Lyskova, Pavlina; Mallatova, Nada; Chlebkova, Jana; Skorepova, Magdalena; Kubatova, Alena; Dobias, Radim; Chudickova, Milada; Kolarik, Miroslav (Medical mycology, 2013)
Auxarthron is a genus within the Onygenales encompassing keratinophilic species with typical ascomata (gymnothecia) consisting of anastomosing network of thick-walled hyphae and small globose or oblate ascospores. No association of this genus with clinically relevant cases of human or animal infection has been reported. This paper describes the isolation of an undescribed Auxarthron species as an agent of proven onychomycosis affecting almost all fingernails in a man with psoriasis. The causality of the isolated fungus was verified by repeated sampling and direct microscopy revealing irregular septate hyphae. Based on micro- and macromorphological features and unique sequence data (ITS region, benA and RPB2 gene), the isolated fungus is proposed as the new species A. ostraviense. The sibling species of A. ostraviense, A. umbrinum, was isolated from three patients with suspected onychomycosis and a detailed clinical history is provided for one of these patients. All four isolates were tested for susceptibility to selected antifungal agents. Terbinafine and clotrimazole appear to be effective in vitro. The morphological identification of Auxarthron spp. is non-trivial, time-consuming and requires cultivation media other than Sabouraud glucose agar which is routinely used in dermatomycology.
Keywords: klotrimazol; Antifungal Agents; DNA, Fungal; terbinafin; Male; psoriáza; naftaleny; onychomykóza; Onychomycosis; Naphthalenes; Sequence Analysis, DNA; sekvenční analýza DNA; Microbial Sensitivity Tests; antifungální látky; molekulární sekvence - údaje; Adult; fungální proteiny; Fungal Proteins; dospělí; mužské pohlaví; Onygenales; mezerníky ribozomální DNA; DNA fungální; lidé; Psoriasis; ženské pohlaví; Humans; mikrobiální testy citlivosti; Terbinafine; DNA, Ribosomal Spacer; Molecular Sequence Data; Female; Clotrimazole; lidé středního věku; Middle Aged